2012
DOI: 10.1088/1674-1056/21/5/050509
|View full text |Cite
|
Sign up to set email alerts
|

Synchronization of impulsively coupled complex networks

Abstract: We investigate the synchronization of complex networks, which are impulsively coupled only at discrete instants. Based on the comparison theory of impulsive differential systems, a distributed impulsive control scheme is proposed for complex dynamical networks to achieve synchronization. The proposed scheme not only takes into account the influence of all nodes to network synchronization, which depends on the weight of each node in the network, but also provides us with a flexible method to select the synchron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…[5][6][7][8] CS means the complete coincidence of the states of all oscillators no matter what the states will be, which appears only if the interacting oscillators are identical. [9][10][11] If the oscillators cannot achieve CS by themselves, various approaches such as linear feedback control, [12][13][14][15] adaptive control, [16][17][18][19] pinning control, [20][21][22][23] time-triggered impulsive control, [24][25][26] event-triggered impulsive control, [27,28] and sampled control [29] have been put forward to guide all the oscillators to reach the desired goal. AD refers to a coupling-induced suppression of oscillating by stabilizing an existing homogeneous steady state.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8] CS means the complete coincidence of the states of all oscillators no matter what the states will be, which appears only if the interacting oscillators are identical. [9][10][11] If the oscillators cannot achieve CS by themselves, various approaches such as linear feedback control, [12][13][14][15] adaptive control, [16][17][18][19] pinning control, [20][21][22][23] time-triggered impulsive control, [24][25][26] event-triggered impulsive control, [27,28] and sampled control [29] have been put forward to guide all the oscillators to reach the desired goal. AD refers to a coupling-induced suppression of oscillating by stabilizing an existing homogeneous steady state.…”
Section: Introductionmentioning
confidence: 99%
“…The study of synchronization among oscillators has a long history. [1][2][3][4][5][6][7] In most works, the effect of oscillators on each other has been assumed to be rapid and without delay, which is an ideal assumption. However, we know that the mutual interaction of oscillators in nature occurs with some delays.…”
Section: Introductionmentioning
confidence: 99%
“…Synchronization of complex dynamical networks has received a great deal of attention from the systems science community in the last decade. [4][5][6][7][8][9][10][11][12][13][14][15] Using the master stability function, [4] Pecora and Carroll developed a general approach to the synchronization of identical dynamical systems. They discovered a bounded synchronization region for the coupling chaotic systems, and showed that if the coupling strength is greater than a threshold, the coupling chaotic systems cannot achieve synchronization.…”
Section: Introductionmentioning
confidence: 99%